D-dimer, BNP/NT-pro-BNP, and creatinine are reliable decision-making biomarkers in life-sustaining therapies withholding and withdrawing during COVID-19 outbreak - Smadja, David M.; Fellous, Benjamin A.; Bonnet, Guillaume; Hauw-Berlemont, Caroline; Sutter, Willy; Beauvais, Agathe; Fauvel, Charles; Philippe, Aurélien; Weizman, Orianne; Mika, Delphine; Juvin, Philippe; Waldmann, Victor; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The decision for withholding and withdrawing of life-sustaining treatments (LST) in COVID-19 patient is currently based on a collegial and mainly clinical assessment. In the context of a global pandemic and overwhelmed health system, the question of LST decision support for COVID-19 patients using prognostic biomarkers arises. Methods: From February 26 to April 20, 2020, 2878 COVID-19 patients hospitalized in a medical department were included in a multicenter study in 24 French hospitals. Based on propensity-matched population, we compared the clinical, biological and management characteristics and survival of patients with and without LST decision using respectively Student's t, Chi2 tests and Cox model. Results: A LST was decided for 591 patients (20.5%). These 591 COVID-19 patients with LST decision were secondarily matched (1:1) on age, sex, body mass index and cancer history with 591 COVID-19 patients with no LST decision. Patients with LST decision had significantly more cardiovascular disease, such as high blood pressure (72.9% vs 66.7%, p=0.02), stroke (19.3% vs 11.1%, p<0.001), renal failure (30.4% vs 17.4%, p<0.001) and heart disease (22.5% vs 14.9%, p<0.001). At admission LST patients were more severe attested by a qSOFA score≥2 (66.5% vs 58.8%, p = 0.03). Biologically, LST patients had significantly higher values of Ddimers, markers of heart failure (BNP and NT-pro-BNP) and renal damage (creatinine) (p <0.001). Their evolution was more often unfavorable (In hospital mortality) than patients with no LST decision (41.5% vs 10.3%, p < 0.001). By combining the three biomarkers (Ddimers, BNP and/or NT-proBNP and creatinine), the proportion of limitations increased significantly with the number of abnormally high biomarkers (24%, 41.3%, 48.3% and 60% respectively for none, one, two and three high value of biomarkers, trend p<0.01). Conclusion: The concomitant increase in Ddimers, BNP/NT-proBNP and creatinine during the admission of a COVID-19 patient could represent a reliable and helpful tool for LST decision. Circulating biomarker might potentially provide additional information for LST decision for COVID-19 patients.